Robust sliding mode control for robot manipulator tracking problem using a proportional-integral switching surface - Ahmad, M. N. (2003)
This paper presents the development of a proportional-integral sliding mode controller for tracking problem of robot manipulators. A robust sliding mode controller is derived so that the actual trajectory tracks the desired trajectory as closely as possible despite the highly non-linear and coupled dynamics. The proportional-integral sliding mode is chosen to ensure the stability of the overall dynamics during the entire period i.e. the reaching phase and the sliding phase. Application to a two-link planar robot manipulator is presented.